2022
DOI: 10.3389/fcvm.2022.802181
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coronary Artery Bypass Grafting and Drug-Eluting Stent Implantation in Patients With Chronic Kidney Disease: A Propensity Score Matching Study

Abstract: ObjectivesTo compare the long-term outcomes of coronary artery bypass grafting (CABG) vs. percutaneous coronary intervention (PCI) with drug-eluting stents (DESs) for coronary artery disease (CAD) patients with chronic kidney disease (CKD).MethodsCoronary artery disease patients with decreased kidney function (estimated glomerular filtration rate <60 ml/min/1.73 m2) who underwent CABG (n = 533) or PCI with DES (n = 952) from 2013 to 2020 were enrolled at a single center. The baseline characteristics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…PSM analysis is statistical method of adjusting for potential baseline confounding variables to simulate a randomized controlled trial design. PSM analysis has increasingly appeared in cardiovascular research [20][21][22][23]. However, we consider that the advantages of one method do not outweigh the other.…”
Section: Discussionmentioning
confidence: 99%
“…PSM analysis is statistical method of adjusting for potential baseline confounding variables to simulate a randomized controlled trial design. PSM analysis has increasingly appeared in cardiovascular research [20][21][22][23]. However, we consider that the advantages of one method do not outweigh the other.…”
Section: Discussionmentioning
confidence: 99%
“…It was 13.90%, 11.41%, and 7.96% for diabetes, hypertension, and CVD, respectively. [123] CKD and Revascularization Therapy for CAD A retrospective single-center study from Anzhen hos-pital compared the long-term outcomes of coronary artery bypass grafting (CABG) vs. percutaneous coronary intervention (PCI) with drug-eluting stents (DES) for CAD patients with CKD. The primary endpoint was the occurrence of all-cause death.…”
Section: Prevalencementioning
confidence: 99%
“…The data in a study from the National Hospital Quality Monitoring System (HQMS) revealed a rapid increase in the proportion of patients experiencing heart failure syndrome among those with both type 1 diabetes (T1DM) and T2DM in tertiary hospitals from 2013 to 2017. ( Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%